Prioritizing emerging contaminants in tropical riverine systems: An integrated approach using ecological and human health risk indices - Muhammad Raznisyafiq Razak; Noraishah Mydin Abdul-Aziz; Singh Nisheljeet; Nawaltul Akma Ahmad Sabri; Muhammad Qusyairi Jori Roslan; Nor Rohaizah Jamil; Didi Erwandi Mohamad Haron; Pao-Chi Liao; Ahmad Zaharin Aris (Regulatory Toxicology and Pharmacology, 2026)

Advancing plastic waste-to-hydrogen: A cross-technology framework integrating eco-technoeconomic analysis, catalyst stability benchmarking and knowledge mapping - Usman Bello; Haruna Adamu; Muhammad Faizan; Abdul Aziz Jallow; Maryem Ourimi; Roa’a Alzoubi; Shafirah Samsuri; Abdul Gani Abdul Jameel; Mohammad Nahid Siddiqui (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to “A review on biohydrogen production through dark fermentation via the lactate pathway” [Bioresour. Technol. 454 (2026) 134726] - Amir Izzuddin Adnan; Hassan Mohamed; Eqwan Roslan; Nur Atiqah Mohamad Aziz; Mouad Firah; Mohd Nur Ikhmal Salehmin; Bidattul Syirat Zainal; Muhammad Fikri Zulkornain; Farah Nurhikmah; Saifuddin Nomanbhay; Peer Mohamed Abdul; Sumaiya Zainal Abidin (Bioresource Technology, 2026)

Bimetallic ferro and lanthanum impregnated on nano HZSM-5 catalysts for the Reutealis trisperma oil hydroprocessing to rich aromatic jet fuel range - Muhammad Al Muttaqii; Abdul Aziz; Sugeng Priyanto; Indri Yati; Muh. Nur Khoiru Wihadi; Amalia Kurnia Amin; Kiky Corneliasari Sembiring; Hendris Hendarsyah Kurniawan; Sudibyo; Didik Prasetyoko; Reva Edra Nugraha; Lenny Marlinda; et al. (Bioresource Technology Reports, 2026)

A review on biohydrogen production through dark fermentation via the lactate pathway - Amir Izzuddin Adnan; Hassan Mohamed; Eqwan Roslan; Nur Atiqah Mohamad Aziz; Mouad Firah; Mohd Nur Ikhmal Salehmin; Bidattul Syirat Zainal; Muhammad Fikri Zulkornain; Farah Nurhikmah; Saifuddin Nomanbhay; Peer Mohamed Abdul; Sumaiya Zainal Abidin (Bioresource Technology, 2026)

Spatiotemporal Distribution of Cyanobacteria in Tropical Freshwater Reservoir and Machine Learning Prediction using Explainable Artificial Intelligence - Muhammad Sarfraz Ahmad Mangat; Teh Sabariah binti Abd Manan; Sharifah Sakinah Syed Abd Mutalib; Zarimah Mohd Hanafiah; Nur Azwa Muhamad Bashar; Salmia Beddu; Nur Liyana Mohd Kamal; Daud Mohamad; Shatha Aser Hamad Aldala’in; Adel Gohari; Wan Hanna Melini Wan Mohtar; Muhammad Raza Ul Mustafa; et al. (Water, Air, & Soil Pollution, 2026)

Synergistic effects of zinc and reduced glutathione application on growth, yield, gas exchange attributes, water relations, and metabolite profiles in Zea mays (L.) plants under water deficit irrigation - Farah Saeed; Qasim Ali; Suliman Mohammed Suliman Alghanem; Abida Kausar; Rashida Perveen; Haifa Abdul Aziz Sakit Alhaithloul; Muhammad Rizwan (South African Journal of Botany, 2026)

GC-MS Profiling, Cytotoxicity and Antiviral Activity of Caulerpa lentillifera and C. macrodisca from Northern Coastal Waters of Borneo Island, Eastern Malaysia - Mohammad Tamrin Mohamad Lal; Elden Sai Long Chang; Zy Chee Wong; Leong Seng Lim; Muhammad Dawood Shah; Wahidatul Husna Zuldin; Gilbert Ringgit; Nur Azreen Arbi; Ahmad Hazim Abdul Aziz; Abdul Aziz Jaziri; Asep Awaludin Prihanto; Attabik Mukhamad Amrillah; et al. (Marine Biotechnology, 2026)

Biochar and Montmorillonite in Combination Improved the Plant growth, physiology, Yield and Decreased Lead (Pb) Uptake in Wheat (Triticum aestivum L.) Under Pb Stress - Zaffar Malik; Suliman Mohammed Suliman Alghanem; Nasir Masood; Hina Rizvi; Muhammad Waseem; Ahmad Ali; Haifa Abdul Aziz Sakit Alhaithloul; Muhammad Rizwan (Journal of Soil Science and Plant Nutrition, 2026)

The influence of community perceptions and practices on the sustainability of Pulau Kapas Marine Park - Muhammad Naqib Hasri; Nazli Aziz; Nurul Huda Sapehee; Nur Qamarina Mohmad Fuad; Ahmad Irsyad Ahmad; Tengku Balkis Tunku Shahar Tengku Abdul Rashid; Nurashiqin Sallih Udin; Abdul Rahman Abdul Latip (Journal of Coastal Conservation, 2026)

Ethnoecology of the Wakhi community in Broghil Valley, Chitral, Pakistan - Hasin Sahar; Lal Badshah; Muhammad Abdul Aziz; Allah Ditta (Genetic Resources and Crop Evolution, 2026)

Thiourea-modified silk cotton carbon as an efficient sulfur host: A green approach for advanced aluminum-sulfur battery - Muhammad Faheem; Arshad Hussain; Ananda Sholeh Rifky Hakim; Muhammad Ali; Abbas Saeed Hakeem; Md. Abdul Aziz (Biomass and Bioenergy, 2025)

Monitoring and optimization of heavy metal phytoextraction in constructed wetlands amended with organic chelators - Mujahid Farid; Ambreen Mussarat; Muhammad Zubair; Zaki ul Zaman Asam; Ayesha Siddiqua; Wajiha Sarfraz; Roha Murtaza; Suliman Mohammed Suliman Alghanem; Haifa Abdul Aziz Sakit Alhaithloul (Environmental Monitoring and Assessment, 2025)

Recent strategy on green synthesis of mesoporous silica from waste for a sustainable and circular economy - Reva Edra Nugraha; Nur Aini Fauziyah; Silvana Dwi Nurherdiana; A.R. Yelvia Sunarti; Abdul Aziz; Ni Ketut Sari; Ajit K. Sarmah; Muhammad Al Muttaqii; Zuhriah Mumtazah; Novia Amalia Sholeha; Hasliza Bahruji; Aishah Abdul Jalil; et al. (Journal of Environmental Chemical Engineering, 2025)

Life cycle greenhouse gas emission reduction potential of alternate wetting and drying in rice cultivation under Malaysian major granary areas - Nurul Ain Abu Bakar; Mohd Saufi Bastami; Muhammad Hariz Abdul Rahman; Rozimah Mohd Rasdi; Mohd Aziz Rashid; Shahida Hashim; Mohd Najib Mohd Yusof; Fauzi Jumat; Mohd Fairuz Md Suptian (Journal of Cleaner Production, 2025)

An overview of ethnobotanical investigations for primary healthcare: a case study from Mardan district, Pakistan - Muhammad Mohsin; Musheerul Hassan; Ivana Vitasović-Kosić; Mona S. Alwahibi; Sher Wali; Qoryog’diyev Zufar Oxunjonovich; Muhammad Abdul Aziz; M. Ajmal Ali; Rainer W. Bussmann; Arshad Mehmood Abbasi (Plant Biosystems, 2025)

Managing Fertilizer Rates and Tillage Depth to Improve Nitrogen Use Efficiency and Soil Health - Abdul Wakeel; Abdul Qadeer; Zunaira Bano; Muhammad Rizwan Shahid; Muhammad Rizwan; Aysha Kiran; Muhammad Sanaullah; Tariq Aziz; Robert Martin Rees; Arti Bhatia; Julia Drewer (Journal of Soil Science and Plant Nutrition, 2025)

Polycyclic aromatic hydrocarbons (PAHs) occurrences in water bodies, extraction techniques, detection methods, and standardized guidelines for PAHs in aqueous solutions - Rana Muhammad Mubeen Muhsin; Teh Sabariah Binti Abd Manan; Joseph Bidai; Muhammad Sarfraz Ahmad Mangat; Zarimah Mohd Hanafiah; Adel Gohari; Naveed Ahmad; Farooq Ahmad; Salmia Beddu; Nur Liyana Mohd Kamal; Daud Mohamad; Shatha Aser Hamad Aldala'in; et al. (Science of The Total Environment, 2025)

Exploring the phytochemical profile, antioxidant activity, and anticancer potential of Achillea millefolium extracts: In-vitro and in-silico investigation - Asia Kiran; Awais Altaf; Muhammad Sarwar; Tahir Maqbool; Muhammad Abdul Basit Ashraf; Muhammad Naveed; Tariq Aziz; Metab Alharbi (South African Journal of Botany, 2025)

Effects of dietary vitamins C and E on growth performance, hematological and biochemical parameters, skeletal abnormalities, and disease resistance against V. harveyi of hybrid groupers (Epinephelus fuscoguttatus♀ × Epinephelus lanceolatus♂) - Isabella Ebi; Rossita Shapawi; Leong-Seng Lim; Annita Seok-Kian Yong; Nurzafirah Mazlan; Muhammad Dawood Shah; Najamuddin Abdul Basri; Abdul Aziz Jaziri (Aquaculture International, 2025)

The importance of sharing: wild plant knowledge in three valleys of Northern Pakistan - Adnan Ali Shah; Abid Raza; Naji Sulaiman; Dipak Khadka; Abdul Majid; Muhammad Abdul Aziz; Arshad Mehmood Abbasi; Mushtaq Ahmad; Andrea Pieroni (Plant Biosystems, 2024)

Light-driven C1 Chemical Conversion with LDH-based Nanomaterials - Zixi Liu; Muhammad Altaf Nazir; Muhammad Altaf; Hammad Majeed; Zeinhom M. El-Bahy; Mohamed H. Helal; Abdul Rauf; Sami Ullah; Tayyaba Najam; Syed Shoaib Ahmad Shah; Aziz ur Rehman (Applied Clay Science, 2024)

Drivers of municipal water security and vulnerability in Pakistan: A case study of Mardan, Khyber Pakhtunkhwa - Kamran; Junaid Aziz Khan; Fasiha Safdar; Umer Khayyam; Iftikhar Hussain Adil; Abdul Waheed; Muhammad Fahim Khokhar (Groundwater for Sustainable Development, 2024)

Smartphone-assimilated colorimetric sensor for sub-nanomolar emamectin detection via KA30 capped silver nanoparticles in food, bio-fluids and water samples - Aziz Balouch; Kashif Hussain; Ayman Nafady; Abdul Jabbar; Sufian Rasheed; Sumaira Kanwal; Sadia Haider; Razium Ali Soomro; Sirajuddin; Muhammad Raza Shah (Food Chemistry, 2024)

Enhancing the CO2 adsorption with dual functionalized coconut shell-hydrochar using Chlorella microalgae and metal oxide: Synthesis, physicochemical properties & mechanism evaluations - Nuradila Zahirah Mohd Azmi; Archina Buthiyappan; Muhammad Fazly Abdul Patah; Nor Adilla Rashidi; Abdul Aziz Abdul Raman (Journal of Cleaner Production, 2024)

Kinetic exploration of CO2 methanation over nickel loaded on fibrous mesoporous silica nanoparticles (CHE-SM) - Muhammad Akmal Aziz; Aishah Abdul Jalil; Nurul Sahida Hassan; Mahadi Bin Bahari; Abdul Hakim Hatta; Tuan Amran Tuan Abdullah; Nurfatehah Wahyuny Che Jusoh; Herma Dina Setiabudi; Rajendran Saravanan (Process Safety and Environmental Protection, 2024)

Florfenicol removal from veterinary pharmaceutical effluents: Tri-metallic zeolite 5A° for electrochemical oxidation and catalytic ceramic membrane separation - Amir Ikhlaq; Maryam Gull; Afnan Sajid; Khurram Saleem Joya; Muhammad Raashid; Osama Shaheen Rizvi; Zafar Masood; Salman Ahmed; Maryam Abid; Maham Hanif; Hafiz Abdul Aziz; Thamer Abdulhameed Al Johani; et al. (Journal of Environmental Chemical Engineering, 2024)

Enantioselective dihydroxylation of xanthorrhizol from Curcuma xanthorrhiza via biotransformation using Aspergillus Niger - Nurul Iman Aminudin; Ahmad Amzar Abdul Aziz; Zaima Azira Zainal Abidin; Deny Susanti; Muhammad Taher (Natural Product Research, 2024)

Giant mud crab shell biochar: A promising adsorbent for methyl violet removal in wastewater treatment - Azrul Nurfaiz Mohd Faizal; Nicky Rahmana Putra; Ahmad Hazim Abdul Aziz; Augustine Agi; Muhammad Abbas Ahmad Zaini (Journal of Cleaner Production, 2024)

Unveiling the green horizon: A bibliometric analysis of global foreign direct investment research and its emphasis on climate change - Muhammad Shabbar Raza; Yusheng Wang; Abdul Rauf; Noshaba Aziz; Muhammad Ajmal Khan; Abid Hussain (Journal of Cleaner Production, 2024)

Algae-derived bioactive compounds as potential pharmaceuticals for cancer therapy: A comprehensive review - Lubna Anjum Minhas; Muhammad Kaleem; Hafiz Muhammad Umer Farooqi; Farzana Kausar; Rooma Waqar; Theophilus Bhatti; Shahid Aziz; Dong Won Jung; Abdul Samad Mumtaz (Algal Research, 2024)

Efficient treatment of veterinary pharmaceutical industrial wastewater by catalytic ozonation process: degradation of enrofloxacin via molecular ozone reactions - Amir Ikhlaq; Zafar Masood; Umair Yaqub Qazi; Muhammad Raashid; Osama Shaheen Rizvi; Hafiz Abdul Aziz; Muhammad Saad; Fei Qi; Rahat Javaid (Environmental Science and Pollution Research, 2024)

Efficient performance of InP and InP/ZnS quantum dots for photocatalytic degradation of toxic aquatic pollutants - Maryam Abbasi; Rukhsanda Aziz; Muhammad Tariq Rafiq; Aziz Ur Rahim Bacha; Zahid Ullah; Abdul Ghaffar; Ghulam Mustafa; Iqra Nabi; Malik Tahir Hayat (Environmental Science and Pollution Research, 2024)

Adopting Marine Spatial Planning (MSP) using coral health assessment as indicator: A case study in Pulau Redang Marine Park, Malaysia - Farhana Razak; Wei Yien Lua; Nor Hafzan Abd Rasid; Nazli Aziz; Izarenah Md Repin; Xiong-Zhi Xue; Abdul Rahman Muhammad Ashraf; Zainudin Bachok; Aminudin Afiq-Firdaus; Wan Izatul Asma Wan Talaat; Abdul Rahman Abdul Latip; Che Din Mohd Safuan (Ocean & Coastal Management, 2024)

Retraction Note: Ameliorative effect of two structurally divergent hydrazide derivatives against DSS-induced colitis by targeting Nrf2 and NF-κB signaling in mice - Ashrafullah Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Sajjad Ahmad; Muhammad Usman Amin; Muhammad Naeem Ahmed; Zia‑ur‑Rehman; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Engineering of metal organic framework (MOF) membrane for waste water treatment: Synthesis, applications and future challenges - Muhammad Umar Shahid; Tayyaba Najam; Mazharul Islam; Ahmed M. Hassan; Mohammed A. Assiri; Abdul Rauf; Aziz ur Rehman; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Journal of Water Process Engineering, 2024)

Developing Micropropagation Protocols of Date Palm (Phoenix dactylifera L.) cv. Barhi Using Shoot Tip Explants - Najamuddin Solangi; Adel Ahmed Abul-Soad; Mushtaque Ahmed Jatoi; Ghulam Sarwar Markhand; Muhammad Aslam Solangi; Abdul Aziz Mirani (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2023)

Retraction Note: Inhibition of NF-κB signaling and HSP70/HSP90 proteins by newly synthesized hydrazide derivatives in arthritis model - Ashraf Ullah Khan; Amna Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Muhammad Naeem Ahmed; Salman Ul Islam; Hussain Ali; Adeeb Shehzad; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Elucidating growth and biochemical characteristics of rice seedlings under stress from chromium VI salt and nanoparticles - Maryam Noor; Arif Ullah; Muhammad Israr Khan; Irum Raza; Muhammad Iqbal; Abdul Aziz; Gil Won Kim; Nadia Taimur; Azizullah Azizullah; Imran Ali; Pil Joo Kim (Environmental Science and Pollution Research, 2023)

Could climate change exacerbate droughts in Bangladesh in the future? - Mahfuzur Rahman; Md Sakib Hasan Tumon; Md Monirul Islam; Ningsheng Chen; Quoc Bao Pham; Kashif Ullah; Sumaiya Jarin Ahammed; Sharmina Naznin Liza; Md Abdul Aziz; Salit Chakma; Muhammad Esmat Enan; Md. Alomgir Hossain; et al. (Journal of Hydrology, 2023)

Occurrence, source identification and ecological risk assessment of heavy metals in water and sediments of Uchalli lake – Ramsar site, Pakistan - Ayesha Aftab; Rukhsanda Aziz; Abdul Ghaffar; Muhammad Tariq Rafiq; Ying Feng; Zafeer Saqib; Muhammad Khalid Rafiq; Muhammad Akbar Awan (Environmental Pollution, 2023)

Interactions of Metal‐Based Engineered Nanoparticles with Plants: An Overview of the State of Current Knowledge, Research Progress, and Prospects - Abdul Wahab; Asma Munir; Muhammad Hamzah Saleem; Mukhtar Iderawumi AbdulRaheem; Humera Aziz; Manar Fawzi Bani Mfarrej; Gholamreza Abdi (Journal of Plant Growth Regulation, 2023)

Wild food plants gathered by four cultural groups in North Waziristan, Pakistan - Noor Khalid; Lal Badshah; Adnan Ali Shah; Arman Ullah; Naushad Khan; Muhammad Abdul Aziz; Renata Sõukand; Andrea Pieroni (Genetic Resources and Crop Evolution, 2023)

Techno-economic analysis of PV systems installed by using innovative strategies for smart sustainable agriculture farms - Yahya Aziz; Abdul Kashif Janjua; Muhammad Hassan; Mustafa Anwar; Saira Kanwal; Muhammad Yousif (Environment, Development and Sustainability, 2023)

RETRACTED ARTICLE: Ameliorative effect of two structurally divergent hydrazide derivatives against DSS-induced colitis by targeting Nrf2 and NF-κB signaling in mice - Ashrafullah Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Sajjad Ahmad; Muhammad Usman Amin; Muhammad Naeem Ahmed; Zia-ur-Rehman; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Nutritional Value of Dry Fish in Bangladesh and Its Potential Contribution to Addressing Malnutrition: A Narrative Review - Md. Hasan Al Banna; Abdullah Al Zaber; Nahidur Rahman; Md Abrar Mozahid Siddique; Muhammad Abu Bakr Siddique; John Elvis Hagan; M. A. Rifat; Christiana Naa Atsreh Nsiah-Asamoah; Abdul-Aziz Seidu; Bright Opoku Ahinkorah; Md Shafiqul Islam Khan (Fishes, 2022)
Understanding the linkage between the nutrient composition of foods and individuals’ recommended nutrient intake is important to address malnutrition. Despite it being a traditional and popular food item in Bangladesh, the nutrient composition of dry fish has not been reviewed yet. This study used a narrative review to assess the nutrient composition of dry fish and estimated its potential contribution to addressing some common nutritional deficiencies among children and pregnant and lactating women in Bangladesh. Records were collected from different databases, including the Web of Science, Google Scholar, PubMed, ScienceDirect, Banglajol, and ResearchGate. Data were extracted from 48 articles containing 1128 entries regarding nutrient composition. Most of the nutrient analyses estimated the proximate composition, whereas vitamin, mineral, amino acid, and fatty acid compositions were scarce in the literature. We found that dry fish has high protein and mineral content and could contribute highly to meeting the recommended nutrient intake of protein, iron, zinc, and calcium for children and pregnant and lactating women. The summarized nutrient composition data could be useful for further research to observe how dry fish could be best utilized to address malnutrition in Bangladesh. This narrative review recommends that further nutrient analysis, with emphasis on vitamin, mineral, and fatty acid compositions.

Pyroptosis in acute pancreatitis and its therapeutic regulation - Abdullah Al Mamun; Suzia Aktar Suchi; Md. Abdul Aziz; Muhammad Zaeem; Fahad Munir; Yanqing Wu; Jian Xiao (Apoptosis, 2022)

The nexus between traditional foraging and its sustainability: a qualitative assessment among a few selected Eurasian case studies - Muhammad Abdul Aziz; Giulia Mattalia; Naji Sulaiman; Adnan Ali Shah; Zbynek Polesny; Raivo Kalle; Renata Sõukand; Andrea Pieroni (Environment, Development and Sustainability, 2022)

Organic geochemical and petrological evaluation to assess the remaining hydrocarbon potential and depositional conditions: a case study of the Paleozoic shales of west Perlis region, northern Peninsular Malaysia - Muhammad Nadzmi Abdul Ghofur; Jasmi Hafiz Abdul Aziz; Yousif M. Makeen; Wan Hasiah Abdullah; Mohammed Hail Hakimi (Arabian Journal of Geosciences, 2022)

Impact of different nitrogen management options and weed competition periods on weed dynamics, productivity, and profitability of bread wheat - Muhammad Saqib; Abdul Khaliq; Asif Tanveer; Tariq Aziz (Arabian Journal of Geosciences, 2022)

Essential oil composition and antibacterial activity of Canarium strictum Roxb. resin - Halima Tahir; Nadeem Muhammad; Azeem Intisar; Muhammad Imran Din; Uzma Qaisar; Muhammad Abdul Qadir; Noor Ul Ain; Zeeshan Ahmad; Pakeeza Aziz; Muhammad Khurram Shahzad; Irshad Hussain (Plant Biosystems, 2021)

Achieving pro-poor growth and environmental sustainability agenda through information technologies: as right as rain - Muhammad Imran; Khan Burhan Khan; Khalid Zaman; Mohammed Borhandden Musah; Elih Sudiapermana; Abdul Rashid Abdul Aziz; Rahimah Embong; Zainudin Bin Hassan; Mohd Khata Jabor; Siti Nisrin Mohd Anis (Environmental Science and Pollution Research, 2021)

RETRACTED ARTICLE: Inhibition of NF-κB signaling and HSP70/HSP90 proteins by newly synthesized hydrazide derivatives in arthritis model - Ashraf Ullah Khan; Amna Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Muhammad Naeem Ahmed; Salman Ul Islam; Hussain Ali; Adeeb Shehzad; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Chemical fractionation and risk assessment of trace elements in sewage sludge generated from various states of Pakistan - Umair Riaz; Ghulam Murtaza; Saifullah; Muhammad Farooq; Humera Aziz; Ayesha Abdul Qadir; Shahzada Munawar Mehdi; Muhammad Akram Qazi (Environmental Science and Pollution Research, 2020)

Characterizing Lentil Germplasm for Zinc Biofortification and High Grain Output - Naser Rasheed; Muhammad Aamer Maqsood; Tariq Aziz; Abdul Jabbar (Journal of Soil Science and Plant Nutrition, 2020)

Response surface methodology and artificial neural network for remediation of acid orange 7 using TiO2-P25: optimization and modeling approach - Muhammad Zulfiqar; Sujan Chowdhury; Abdul Aziz Omar; Ahmer Ali Siyal; Suriati Sufian (Environmental Science and Pollution Research, 2020)

An Integrated Systems Biology and Network-Based Approaches to Identify Novel Biomarkers in Breast Cancer Cell Lines Using Gene Expression Data - Abbas Khan; Zainab Rehman; Huma Farooque Hashmi; Abdul Aziz Khan; Muhammad Junaid; Abrar Mohammad Sayaf; Syed Shujait Ali; Fakhr Ul Hassan; Wang Heng; Dong-Qing Wei (Interdisciplinary Sciences: Computational Life Sciences, 2020)

Detection of QTLs for outcrossing-related traits in rice (Oryza sativa L.) by association mapping and the RSTEP-LRT method - Lal Bux; Dalu Li; Muhammad Faheem; Ognigamal Sowadan; Zhiyao Dong; Erbao Liu; Mehtab Ali; Yanhui Li; Helder Manuel Sitoe; Abdul Aziz Mirani; Delin Hong (Euphytica, 2019)

Variants in KIAA0825 underlie autosomal recessive postaxial polydactyly - Irfan Ullah; Naseebullah Kakar; Isabelle Schrauwen; Shabir Hussain; Imen Chakchouk; Khurram Liaqat; Anushree Acharya; Naveed Wasif; Regie Lyn P. Santos-Cortez; Saadullah Khan; Abdul Aziz; Kwanghyuk Lee; et al. (Human Genetics, 2019)

Ameliorative Effects of Selenium in ZnO NP-Induced Oxidative Stress and Hematological Alterations in Catla catla - Muhammad Saleem Asghar; Naureen Aziz Qureshi; Farhat Jabeen; Muhammad Saleem Khan; Muhammad Shakeel; Abdul Shakoor Chaudhry (Biological Trace Element Research, 2018)

Bioaccumulation of heavy metals and analysis of mineral element alongside proximate composition in foot, gills and mantle of freshwater mussels (Anodonta anatina) - Muhammad Sohail; Muhammad Naeem Khan; Abdul Shakoor Chaudhry; Naureen Aziz Qureshi (Rendiconti Lincei. Scienze Fisiche e Naturali, 2016)

Zinc nutrition in rice production systems: a review - Hafeez-ur Rehman; Tariq Aziz; Muhammad Farooq; Abdul Wakeel; Zed Rengel (Plant and Soil, 2012)

Assessment of radiological hazard of NORM in Margalla Hills limestone, Pakistan - Muhammad Ali; Aziz Ahmed Qureshi; Abdul Waheed; Muzahir Ali Baloch; Hamza Qayyum; Muhammad Tufail; Hameed Ahmed Khan (Environmental Monitoring and Assessment, 2012)

Synthesis, characterization, and urease inhibition of 5-substituted-8-methyl-2H-pyrido[1,2-a]pyrimidine-2,4(3H)-diones - Abdul Rauf; Sumaira Liaqat; Ashfaq M. Qureshi; Muhammad Yaqub; Aziz U. Rehman; Mahmood U. Hassan; Zahid H. Chohan; Faiz U. H. Nasim; T. Ben Hadda (Medicinal Chemistry Research, 2012)

Serum Electrolyte and Mineral Variations During Pregnancy and Lactation in Nili-Ravi Buffalo - M. Saleem Akhtar; Abdul Asim Farooq; Syed Aun Muhammad; Laeeq Akbar Lodhi; C. Sikandar Hayat; M. Mushtaq Aziz (Biological Trace Element Research, 2010)

Monoterpene glycosides from Indigofera hetrantha - Sajid Mehmood; Aziz-Ur-Rahman; Zaheer Ahmad; Nighat Afza; Abdul Malik; Habib Ahmad; Muhammad Iqbal Choudhary (Natural Product Research, 2008)

Effect of seedling age and water depth on morphological and physiological aspects of transplanted rice under high temperature - Abdul Aziz Khakwani; Masaaki Shiraishi; Muhammad Zubair; Mohammad Safdar Baloch; Khalid Naveed; Inayatullah Awan (Journal of Zhejiang University-SCIENCE B, 2005)